Memahami Konsep Sakral dan Profan dalam Agama-Agama - Nurdinah Muhammad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
In the religious context of everyday life, sometimes it is difficult to  distinguish between something that is pure religion and the ideas or interpretations  of religion. Something pure religion, comes from God, the absolute and contain  sacred values. The ideas of religion, meaning comes from other than God  (Human), temporal, changing, and not sacred (profane). In the realization of  aspects, sometimes have difficulty distinguishing the two because of overlap and  confusion of meaning occurs between religion and religious thought, whether  intentionally or not. Subsequent developments, results sometimes religious  thought has turned into a religion itself, so it is considered sacred and sinful for  those who are trying, breaking and change it. In this case raises questions among  some communities; What religion is part of culture or religion or culture in every  culture, religion is the most valuable part of the whole social life